Functional Tissue Analysis Reveals Successful Cryopreservation of Human Osteoarthritic Synovium - Broeren, Mathijs G. A. (PLoS One, 2016)
Osteoarthritis (OA) is a degenerative joint disease affecting cartilage and is the most common form of arthritis worldwide. One third of OA patients have severe synovitis and less than 10% have no evidence of synovitis. Moreover, synovitis is predictive for more severe disease progression. This offers a target for therapy but more research on the pathophysiological processes in the synovial tissue of these patients is needed. Functional studies performed with synovial tissue will be more approachable when this material, that becomes available by joint replacement surgery, can be stored for later use. We set out to determine the consequences of slow-freezing of human OA synovial tissue. Therefore, we validated a method that can be applied in every routine laboratory and performed a comparative study of five cryoprotective agent (CPA) solutions. To determine possible deleterious cryopreservation-thaw effects on viability, the synovial tissue architecture, metabolic activity, RNA quality, expression of cryopreservation associated stress genes, and expression of OA characteristic disease genes was studied. Furthermore, the biological activity of the cryopreserved tissue was determined by measuring cytokine secretion induced by the TLR ligands lipopolysaccharides and Pam3Cys. Compared to non frozen synovium, no difference in cell and tissue morphology could be identified in the conditions using the CS10, standard and CryoSFM CPA solution for cryopreservation. However, we observed significantly lower preservation of tissue morphology with the Biofreeze and CS2 media. The other viability assays showed trends in the same direction but were not sensitive enough to detect significant differences between conditions. In all assays tested a clearly lower viability was detected in the condition in which synovium was frozen without CPA solution. This detailed analysis showed that OA synovial tissue explants can be cryopreserved while maintaining the morphology, viability and phenotypical response after thawing, offering enhanced opportunities for human in vitro studies.